PENERAPAN MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA PEMBELAJARAN IPA KELAS V SDN KEMBANGAN SELATAN 03 - Natasya Zahrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to obtain data on improving students' scientific literacy using the RADEC (Read, Answer, Discuss, and Explain) learning model in science learning for fifth-grade students of SDN Kembangan Selatan 03 with a total of 29 students. This study was conducted in fifth-grade students of SDN Kembangan Selatan 03 in June 2025. The research method used in this study is Classroom Action Research which adapts the Kemmis & Mc Taggart model and is carried out in two cycles where each cycle consists of planning, implementation, observation, and reflection stages. The results of the study show that the percentage of students' scientific literacy data acquisition in cycle I is 72%. In cycle II there is an increase of 90%. While the data for monitoring teacher actions in science learning through the RADEC learning model in cycle I is 84% and has increased in cycle II, namely 97%. While the data for monitoring student actions in science learning through the RADEC learning model has increased from cycle I 81% to 95%. Thus, from the research results, it can be concluded that the RADEC learning model can improve students scientific literacy in science learning for class V at SDN Kembangan Selatan 03.